2020
DOI: 10.2340/16501977-2615
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the effects of exercise on cognition post-stroke: Secondary analysis of a randomized controlled trial

Abstract: LAY ABSTRACTExercise can improve thinking and memory in people with stroke, but we do not know if men and women improve to the same degree. This study examined whether there were differences in thinking and memory between men and women with stroke after 6 months of aerobic or balance/flexibility exercise. Volunteers were randomly assigned to a 6-month aerobic exercise programme or a balance/flexibility exercise programme. Thinking and memory skills were tested before and after the exercise programme. Women did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Interestingly, when neuroblastic rat cells in culture are treated with the serum from individuals with stroke achieving HIIT, it results in a higher increase of dendritic growth and mitochondria redistribution along these new dendrites [35]. Other authors also found very low effects of long-term "high-intensity training" (not HIIT in this study) on short-term memory without altering working memory and executive functions [23,27]. Indeed, Tang et al, showed no effect on working memory, attention and conflict resolution when exercise intensity progressively increased from 40 to 80% of HR reserve over 3 ➚ Serum BDNF after HIIT ➚ Dendritic growth with patient serum after HIIT ➚ indicate an increase; ⟺ indicate a maintenance; BDNF: brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity.…”
Section: In Rodentssupporting
confidence: 46%
See 2 more Smart Citations
“…Interestingly, when neuroblastic rat cells in culture are treated with the serum from individuals with stroke achieving HIIT, it results in a higher increase of dendritic growth and mitochondria redistribution along these new dendrites [35]. Other authors also found very low effects of long-term "high-intensity training" (not HIIT in this study) on short-term memory without altering working memory and executive functions [23,27]. Indeed, Tang et al, showed no effect on working memory, attention and conflict resolution when exercise intensity progressively increased from 40 to 80% of HR reserve over 3 ➚ Serum BDNF after HIIT ➚ Dendritic growth with patient serum after HIIT ➚ indicate an increase; ⟺ indicate a maintenance; BDNF: brain-derived neurotrophic factor; VEGF: vascular endothelial growth factor; IGF-1: insulin-like growth factor 1; HRR: heart rate reserve; HI: high-intensity; LI; low-intensity; HIIT: high-intensity interval training; MICT: moderate-intensity.…”
Section: In Rodentssupporting
confidence: 46%
“…Interestingly, when neuroblastic rat cells in culture are treated with the serum from individuals with stroke achieving HIIT, it results in a higher increase of dendritic growth and mitochondria redistribution along these new dendrites [ 35 ]. Other authors also found very low effects of long-term “high-intensity training” (not HIIT in this study) on short-term memory without altering working memory and executive functions [ 23 , 27 ]. Indeed, Tang et al, showed no effect on working memory, attention and conflict resolution when exercise intensity progressively increased from 40 to 80% of HR reserve over 3 months of training by using the Verbal Digit Span Test, Color-Word Stroop test and Trail-Making Test Part B [ 23 ] ( Table 1 ).…”
Section: Hiit Could Contribute To Neuroplasticity and Cognitive Rementioning
confidence: 48%
See 1 more Smart Citation
“…And there were more men when considering the total number of participants. The secondary analysis of Tang's study also found female stroke survivors benefited more in set shifting and response inhibition (Khattab et al, 2019). Females had greater progression in white matter hyperintensity while this change in males was not significant according to report from Liu-Ambrose (Dao et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
“…A total of 80 articles were retrieved for fulltext review. There were two studies producing more than one publication (Tang et al, 2014(Tang et al, , 2016Liu-Ambrose et al, 2016;Hsu et al, 2017Hsu et al, , 2018Dao et al, 2019;Khattab et al, 2019), they were regarded as one study in the quantitative analysis. One publication (Rosenfeldt et al, 2019) was the secondary analysis of two randomized controlled trials (ClinicalTrials.gov registration numbers NCT02076776, National Institutes of Health, and NCT02494518, American Heart Association).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%